The Implementing a Carbon Tax as a Means of Increasing Investment Value in Indonesia - Brata, Al Fadilla Yoga; Sedera, Rakotoarisoa Maminiaina Heritiana (Lembaga Contrarius Indonesia, 2023)
The impact of a carbon tax in Indonesia, where it could lessen environmental changes, generate income economically, and raise the value of investments in renewable energy, is described and examined in this study. Doctrinal legal research is the research methodology used. To reach logical conclusions about legal issues, doctrine research is used. Research work can be made more qualified by using legal research. Carbon emissions in Indonesia have been significantly reduced by 13.917% due to the urgency of implementing a carbon tax, and worldwide carbon emissions have decreased by 14.292%. Investments in a mix of renewable energy sources gain value. The implementation of a carbon tax may need help. The political system and the administration of governmental institutions are barriers to implementing the carbon tax—the impact of the economy and business on public disapproval. The government sets revenue management by its objectives, the carbon tax policy is associated with an energy sustainability policy, and the coalition is tightened as part of the strategy to address these issues.